2014
DOI: 10.1016/j.optmat.2014.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Cz grown 2-in. size Ce:Gd3(Al,Ga)5O12 single crystal; relationship between Al, Ga site occupancy and scintillation properties

Abstract: 2inch size Ce1%:Gd 3 (Al 1-x Ga x) 5 O 12 (GAGG) single crystals with various Ga concentration of x=2, 2.4, 2.7 and 3 were grown by the Czochralski (Cz) method. Light yield has maximum value of 58000 photon/MeV at x=2.7 Ga concentration. Energy resolution was improved with decreasing Ga concentration and x=2.4 sample showed best energy resolution of 4.2%@662keV. The dependence of scintillation properties on crystal structure and AlGa was discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
85
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 167 publications
(88 citation statements)
references
References 10 publications
2
85
0
1
Order By: Relevance
“…This result is in good correlation with the high LY in Tb 1.5 Gd 1.5 Al 3-2.5 Ga 2-2.5 O 12 :Ce (BaO) SCFs (Table 1), due to the low Ba 2+ contamination and related with them ptrapping centers as well as to the additional elimination of the trap-related phenomena in the scintillation processes in these SCFs by Ga 3+ and Gd 3+ alloying. Thus, the Ga 3+ alloying in the concentration range y = 2-2.5 positively affects not only the scintillation properties of melt-grown mixed garnet crystals with a large concentration of antisite defects and oxygen vacancies [22][23][24] but antisite free SCF counterparts as well [31][32][33] due to burying the trap levels by the bottom of the conductive band in the Ga-containing garnets. The additional positive effect on the elimination of the trap centers in scintillation phenomena, which is observed in Tb3−xGdxAl5−xGaxO12:Ce SCF samples, is most probably caused by burying the deeper trap levels by high-energy states of Tb 3+ and Gd 3+ cations in such Tb,Gd-rich garnets [36].…”
Section: Tsl Propertiesmentioning
confidence: 99%
“…This result is in good correlation with the high LY in Tb 1.5 Gd 1.5 Al 3-2.5 Ga 2-2.5 O 12 :Ce (BaO) SCFs (Table 1), due to the low Ba 2+ contamination and related with them ptrapping centers as well as to the additional elimination of the trap-related phenomena in the scintillation processes in these SCFs by Ga 3+ and Gd 3+ alloying. Thus, the Ga 3+ alloying in the concentration range y = 2-2.5 positively affects not only the scintillation properties of melt-grown mixed garnet crystals with a large concentration of antisite defects and oxygen vacancies [22][23][24] but antisite free SCF counterparts as well [31][32][33] due to burying the trap levels by the bottom of the conductive band in the Ga-containing garnets. The additional positive effect on the elimination of the trap centers in scintillation phenomena, which is observed in Tb3−xGdxAl5−xGaxO12:Ce SCF samples, is most probably caused by burying the deeper trap levels by high-energy states of Tb 3+ and Gd 3+ cations in such Tb,Gd-rich garnets [36].…”
Section: Tsl Propertiesmentioning
confidence: 99%
“…A more detailed study of the role of Gd 3+ subsystem in the energy transfer processes in garnet crystals plays important role in future optimization of these crystals for exploiting as scintillation material. In particular, scintillation crystals and phosphors based on mixed garnets doped with cerium attract considerable interest due to ability of manipulation with their luminescent and scintillation properties by changing the Al/Ga ratio in the compound [13]. This ability is enabled by the change in the strength of the crystal field acting on the activator ions and, consequently, by shifting the energy levels of Ce 3+ relative to the bottom of the conduction band.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, optimization of garnet composition serves also for the enhancement of the light yield of these scintillators [14]. The most impressive results have recently been achieved in GAGG:Ce, where the scintillation yield of up to 58000 ph/MeV was demonstrated both in single crystals and transparent ceramics [13,15].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Kamada et al have done extensive combinatorial band gap engineering for multi-component garnet compounds and found that crystals of Gd 3 (Ga,Al) 5 O 12 as very promising host materials due to their high density, broad transmission range, and easy doping with rare earth elements like Ce [10,11]. The ratio of Ga and Al in the compound has been found to significantly affect the scintillation and optical properties [12]. Kamada et al have reported that the maximum light yield of 58,000 ph/MeV was obtained with Ga 2.7 Al 2.3 combination while the best energy resolution of 4.2% at 662 keV was achieved with Ga 2.4 Al 2.6 combination [12].…”
mentioning
confidence: 99%
“…The ratio of Ga and Al in the compound has been found to significantly affect the scintillation and optical properties [12]. Kamada et al have reported that the maximum light yield of 58,000 ph/MeV was obtained with Ga 2.7 Al 2.3 combination while the best energy resolution of 4.2% at 662 keV was achieved with Ga 2.4 Al 2.6 combination [12]. Among several possible combinations, the Gd 3 Ga 3 Al 2 O 12 (GGAG) was found to have the best combination of high scintillation light output and fast decay time [10].…”
mentioning
confidence: 99%